Relationship between physical performance and unforced error during the competition in national Turkish junior badminton players - Hotaman, F.; Özgür, B. (International Journal of Applied Exercise Physiology, 2020)
The goal of this study was to examine the relationship between physical performance and unforced errors during the competition in national junior Turkish badminton players. Five male badminton players have participated in the study. Body height, body weight, body mass index have been measured, and 20 m speed, 20 m backward speed, 20 m reaction speed, t-test (agility), flexibility, hand-grip, back and leg strength, standing long jump, vertical jump, medicine ball throw, and 20-m shuttle run tests have been performed to the athletes. Unforced errors have been analysed as out and net errors in the front, middle and rear court areas during competitions. These analyses of the athletes have been conducted in five consecutive tournaments over a three-month tournament period, and a total of 43 matches have been analysed. Spearman's rank correlation coefficient results have shown a significant negative correlation between lower limb power (r=-.90), back strength (r=-.89) and flexibility (r<-.99) with unforced errors, whereas body weight (r=.97), body mass index (r>.99), upper limb power (r>.99), speed (r=-.90), hand-grip strength (r=.89) with unforced errors have shown a significant positive correlation. The results of the presented study emphasize that the physical performance of junior badminton players playa significant role in unforced errors during competitions.